Development and bench testing of a new generator-drive set for railway cars - P. Yu. Semenov; S. L. Samoshkin; A. N. Makarov (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. Air conditioning systems installed in passenger carriages are currently powered using a gear-cardan drive connected to the middle part of the axis of a WBA-32/2 wheel pair designed by Flender (Germany) or its domestically manufactured analogues. Such drive dates back to the mid 1960s in terms of development and implementation. The article is devoted to the development and testing of a new generator-drive set for passenger carriages.Materials and methods. The authors analysed the long-standing operation of the drive according to railway services involved in the maintenance and repair of passenger carriages equipped with air conditioning systems. Bench tests were carried out to test a pilot batch of the main units of the generator-drive set, such as gearbox, couplings and generator.Results. A single-piece generator-drive set was developed and included a gearbox, generator, safety coupling and a elastic coupling. The entire structure of the set is installed on a bogie frame using three supporting elements of the suspension system.Discussion and conclusion. The completed calculations and experimental studies show that the single-piece generatordrive set features parameters that significantly exceed those of series-produced peers. The design of 68-4066 and 68-4096 bogies was modified in order to enable the installation of a new generator-drive set on passenger carriages series-produced bogies. The completed calculation and graphical analyses demonstrates that the new generator-drive set could be installed on 18-6960 high-speed bogies frame.